Upaya Pencegahan Covid-19 Melalui Pembagian Masker Serta Minuman Bergizi Kepada Masyarakat Banjarbaru dan Martapura - Lena Rosida; Triawanti Triawanti; Asnawati Asnawati; Didik Dwi Sanyoto; Roselina Panghiyangani; Lisda Hayatie (Prosiding Konferensi Nasional Pengabdian Kepada Masyarakat dan Corporate Social Responsibility (PKM-CSR), 2020)
COVID-19 cases in Indonesia are increasing as of April 10, reaching 3512 people who have been declared infected with COVID-19, with a death toll of 306 people (8.71%). One of the prevention efforts is to use mask and hand sanitizer and increase immunity status through consumption of nutritious food and drinks. Prevention efforts will work well if we invite the public to participate actively, one of which is the Khosya Berbagi community in Banjarbaru.This activity aims to distribute masks, hand sanitizers and nutritious drinks to the people of Banjarbaru and Martapura, especially those who are vulnerable and have a high risk of being infected with COVID-19. The methods used include identifying people who are prone to infection and have a high risk of infection, making mask, COVID-19 prevention stickers, packaging mask and nutritious drinks, namely honey and milk, followed by distributing gifts to the community. This activity has succeeded in distributing 500 packages consisting of cloth mask, nutritious drinks and hand sanitizer to small traders, pedicab drivers, motorcycle taxi drivers, and road cleaners in Banjarbaru and Martapura. This parcel is also equipped with stickers on efforts to prevent COVID-19. It is hoped that this activity can help people protect themselves from COVID-19.